High responders to hypertrophic strength training also tend to lose more muscle mass and strength during detraining than low responders - Räntilä, A.; Ahtiainen, J. P.; Avela, J.; Restuccia, J.; Kidgell, D.; Häkkinen, K. (The Journal of Strength and Conditioning Research, 2021)
This study investigated differences in individual responses to muscle hypertrophy during strength training and detraining. Ten weeks of resistance training was followed by 6 weeks of detraining in men (n = 24). Bilateral leg press (LP) one-repetition maximum (1RM) and maximal electromyography (EMGs) of vastus lateralis (VL) and vastus medialis, maximal voluntary activation (VA), transcranial magnetic stimulation for corticospinal excitability (CE), cross-sectional area of VL (VLCSA), selected serum hormone concentrations were measured before and repeatedly during training and detraining. In the total group, VLCSA increased by 10.7% (p = 0.025) and LP 1RM by 16.3% (p < 0.0001) after training. The subjects were split into 3 groups according to increases in VLCSA: high responders (HR) > 15% (n = 10), medium responders (MR) 15-4.5% (n = 7), and low responders (LR) < 4.5% (n = 7). Vastus lateralis CSA in HR and MR increased statistically significantly from pre to posttraining but not in LR. Only HR increased LP 1RM statistically significantly from pre to post. Maximal EMG activity increased 21.3 ± 22.9% from pre- to posttraining for the total group (p = 0.009) and for MR (p < 0.001). No significant changes occurred in VA and CE or serum hormone concentrations. During detraining, HR showed a decrease of -10.5% in VLCSA, whereas MR and LR did not. None of the subgroups decreased maximal strength during the first 3 weeks of detraining, whereas HR showed a slight (by 2.5%) rebound in strength. The present results suggest that strength gains and muscle activation adaptations may take place faster in HR and decrease also faster compared with other subgroups during detraining.